2021
DOI: 10.1016/j.kint.2021.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Kidney pericyte hypoxia-inducible factor regulates erythropoiesis but not kidney fibrosis

Abstract: Prolyl hydroxylase domain enzyme (PHD) inhibitors are effective in the treatment of chronic kidney disease (CKD)associated anemia by stabilizing hypoxia inducible factor (HIF), thereby increasing erythropoietin and consequently erythropoiesis. However, concern for CKD progression needs to be addressed in clinical trials. Although preclinical studies showed an anti-inflammatory effect in kidney disease models, the effect of PHD inhibitors on kidney fibrosis was inconsistent probably because the effects of HIF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…The effects of HIFs may be cell type and context dependent. HIF-2 α may also be a candidate for studying renal fibrosis [ 17 , 18 ]. However, HIF-3 is less well known.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of HIFs may be cell type and context dependent. HIF-2 α may also be a candidate for studying renal fibrosis [ 17 , 18 ]. However, HIF-3 is less well known.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that PHDi could not increase HIF2α expression of 10T1/2 cells in the presence of TGF-β1. However, PHDi emerges as a promising therapeutic agent for the renal anemia principally through stabilizing HIF [ 47 49 ]. One of the plausible reasons would be that a continuous spectrum existed between normal kidney pericytes and scar-producing myofibroblasts in fibrotic kidneys [ 3 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that Gli1 is one of the markers of pericyte and the ablation of Gli1 + -cell attenuated renal fibrosis [ 36 ]. Hence, we induced Gli1 + cell-specific HIF stabilization via Vhl or Phd2 knockout showed increased serum erythropoietin and polycythemia without a significant difference in profibrotic gene expression and kidney fibrosis [ 37 ]. However, because there are many other markers of fibroblasts/pericytes such as platelet-derived growth factor (PDGF) receptor β, CD73, smooth muscle myosin protein, and tenascin-C which manifest as different lineages, we need further study to clarify the effect of HIF activation in pericytes from other lineages in various models (ischemia-reperfusion, adenine-induced CKD, aristolochic acid nephropathy, and diabetic nephropathy) and clinical trials to observe the effect of PHD inhibitors on renal fibrosis [ 38 ].…”
Section: The Pleotropic Effects Of Prolyl Hydroxylase Domain Inhibitionmentioning
confidence: 99%